2020
DOI: 10.1111/epi.16643
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe regions essential for preserved picture naming after left temporal epilepsy surgery

Abstract: Objective: To define left temporal lobe regions where surgical resection produces a persistent postoperative decline in naming visual objects. Methods: Pre-and postoperative brain magnetic resonance imaging data and picture naming (Boston Naming Test) scores were obtained prospectively from 59 people with drug-resistant left temporal lobe epilepsy. All patients had left hemisphere language dominance at baseline and underwent surgical resection or ablation in the left temporal lobe. Postoperative naming assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 51 publications
(110 reference statements)
5
39
1
Order By: Relevance
“…These results together contribute to a better understanding of how semantic cognition drives word retrieval. Previous literature has suggested that the left ventral ATL and occipitotemporal regions may serve the multimodal binding involved in word meaning association (Binney et al, 2010;Pulvermüller, 2013;Forseth et al, 2018;Binder et al, 2020). However, our results revealed that the left inferior occipitotemporal region (i.e., the left OTSm or anterior VWFA) acts as a heteromodal word-meaning binding site.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…These results together contribute to a better understanding of how semantic cognition drives word retrieval. Previous literature has suggested that the left ventral ATL and occipitotemporal regions may serve the multimodal binding involved in word meaning association (Binney et al, 2010;Pulvermüller, 2013;Forseth et al, 2018;Binder et al, 2020). However, our results revealed that the left inferior occipitotemporal region (i.e., the left OTSm or anterior VWFA) acts as a heteromodal word-meaning binding site.…”
Section: Discussioncontrasting
confidence: 82%
“…These anatomic and functional areas have long been considered heteromodal integration regions, and recent findings corroborate that posterior parts of the lateral MTG, ITG, and middle FG are centrally involved in representing lexical items independently of modalities (Forseth et al, 2018;Evans et al, 2019;Mattioni et al, 2020). Latest studies with epilepsy patients that used naming tasks to tag the word processing uncovered that the middle occipitotemporal cortex (i.e., FG and ITG) may function as lexical semantic hub and play a crucial part in associating words and their meaning (Forseth et al, 2018;Binder et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…It has been shown that laser ablation of the hippocampus and amygdala reduces the risk of postoperative naming impairment in comparison to standard ATL procedures. 52,59,60,61 Concordantly, we did not find a significant association between the hippocampus and naming performance, and less than 3% of voxels included in the significant cluster belonged to the hippocampus. Additionally, the percentage of the hippocampus removed or ablated was not significantly correlated with a change in BNT performance.…”
Section: Discussionsupporting
confidence: 57%
“…It is widely accepted that language involves a more distributed network than Broca's and Wernicke's area and that anatomically dissociable regions exist that are specialized for specific linguistic subroutines which interactively support the construct of language (34, 39, 150, 151). Regions spanning the ventral temporal and occipital lobes and fusiform area appear to contribute heavily to recognition (primarily right hemisphere, but some left) of visual objects and faces, while coexisting areas on the left are important for naming (152)(153)(154)(155)(156). Naming itself is a complex (161)].…”
Section: Languagementioning
confidence: 99%